A cost-benefit analysis of pre-sorting using a feller-buncher in underdeveloped short rotation poplar plantations. Issue 1 (2nd January 2023) - Spinelli, Raffaele; Magagnotti, Natascia; Kováč, Barnabáš; Heger, Patrik; Heilig, David; Heil, Bálint; Kovács, Gábor; Mihelič, Matevž
ABSTRACT: Underdeveloped tree crops (⩽ 30 bone-dry tons ha −1 ) offer a main harvest of biomass-trees, which lack the size and the form for producing a log. However, about 1/3 of the available stems may yield at least one log, which could significantly increase the overall value of the harvest. Under those circumstances, it may make sense to sort log-trees from biomass-trees at an early stage, rather than having a harvester or a processor go through all of the treesonly to toss almost 70 out of 100 trees into the biomass pile. The Authors set up a controlled experiment to quantify the eventual benefit obtained by early pre-sorting, performed by the feller-buncher. Pre-sorting resulted in a 15% productivity loss for the feller-buncher, which was repaid by a 100% productivity increase for the processor. Considering the different hourly cost of the two machines, three Euros were saved for each additional Euro invested in pre-sorting. Pre-sorting made whole-tree harvesting (WTH) a significantly cheaper option than cut-to-length (CTL), whereas the two systems would be almost equally expensive when no pre-sorting was applied. Pre-sorting would also facilitate multiple-tree delimbing, implemented through the introduction of a chainflail; that is likely to further reduce harvesting cost, returning financial viability to the harvesting of underdeveloped plantations.